The Influence of Collective Behavior on Pacing in Endurance Competitions - Renfree, Andrew; Crivoi do Carmo, Everton; Martin, Louise; Peters, Derek M. (Frontiers in Physiology, 2015)
A number of theoretical models have been proposed to explain pacing strategies in individual competitive endurance events. These have typically related to internal regulatory processes informing the making of decisions relating to muscular work rate. Despite a substantial body of research investigating the influence of collective group dynamics on individual behaviours in various animal species, this issue has not been comprehensively studied in individual athletic events. This is surprising given that athletes directly compete in close proximity to one another, and that collective behaviour has also been observed in other human environments. Whilst reasons for adopting collective behaviour are not fully understood, it is thought to result from individual agents following simple local rules resulting in seemingly complex large systems acting to confer some biological advantage to the collective as a whole. Although such collective behaviours may generally be beneficial, endurance events are complicated by the fact that increasing levels of physiological disruption as activity progresses may compromise the ability of individuals to continue to interact with other group members. This could result in early fatigue and relative underperformance due to suboptimal utilisation of physiological resources by some athletes. Alternatively, engagement with a collective behaviour may benefit all due to a reduction in the complexity of decisions to be made and a subsequent reduction in cognitive loading and mental fatigue. This paper seeks evidence for collective behaviour in previously published analyses of pacing behaviour and proposes mechanisms through which it could potentially be either beneficial, or detrimental to individual performance.